Art Network Strategy, Digitalization for Management Efficiency and Tourists: Bah Koh Samet Island, Chumphon Province, Thailand - Pernandus Simanullang (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Art Network Strategy, Digitalization for Management Efficiency and Tourists. This study aims to analyze art management strategies that affect Bah Koh Samet tourism satisfaction after the covid-19 pandemic. The samples and analyzes were tourists visiting by collecting data in Bann Koh Samet, Chumphon province. Data research using descriptive qualitative includes documentation, interviews, observations, and presentations of several questionnaires. The results found that the hypothesis shows that the consistency between the efficiency of art management and art networking strategies is inconsistent due to a drastic reduction in visitors. Then the art networking strategy provides empirical opportunities to find alternatives to bring in visitors by facilitating the digitization model. Then, the art management strategy with the concept of digitization is carried out by analyzing the advantages and disadvantages of SWOT as a start to better know the target market and the direction of the object of application of the digitalization strategy model.